Communication of the Anterior Branch of the Great Auricular Nerve with the Cervical Branch of Facial Nerve and its Variant Nerve Endings Deep in the Parotid Gland - Rao Sirasanagandla,Srinivasa (Sociedad Chilena de Anatomía, 2012)
The communications between the branches of cervical plexus and cervical branch of facial nerve are common and are well known. However, this communication usually occurs between the transverse cervical nerve and cervical branch of facial nerve. During routine dissection classes for the Medical undergraduate students, we came across an anatomical variant of anterior division of great auricular nerve. This variation was found in a 60-year-old male cadaver of South Indian origin and it was unilateral. The great auricular nerve arose from the loop of ventral rami of C2 and C3 spinal nerves and divided into anterior and posterior branches. The anterior branch ran obliquely upwards and forwards on the surface of the sternocleidomastoid muscle along with the external jugular vein towards the apex of parotid gland and divided into many branches. One of these branches gave a communicating branch to cervical branch of facial nerve outside the parotid gland. Nerve endings of the remaining branches were found to penetrate the interlobular septa and a few of them were seen deep in the gland along the ducts and near the vessels. The functional significance of anatomic variations of nerve endings in relation to ducts, thin vessels deep in the parotid gland, observed in the present case are yet to be evaluated.